Humanitarian crises and migration : causes, consequences and responses - Martin, Susan Forbes; Weerasinghe, Sanjula S.; Taylor, Abbie, 1988- (Abingdon, Oxon ; New York : Routledge, 2014)
"This timely book brings together leading experts from multi-disciplinary backgrounds to reflect on diverse humanitarian crises and to shed light on a series of exploratory questions: In what ways do people move in the face of crisis situations? Why do some people move, while others do not? Where do people move? When do people move, and for how long? What are the challenges and opportunities in providing protection to crisis migrants? How might we formulate appropriate responses and sustainable solutions, and upon what factors should these depend? This book is divided into four parts, with an introductory section outlining the parameters of 'crisis migration', conceptualizing the term and evaluating its utility. This section also explores the legal, policy and institutional architecture upon which current responses are based. Section Two presents a diverse set of case studies, from the earthquake in Haiti and the widespread violence in Mexico, to the on-going exodus from Somalia and environmental degradation in Alaska and the Carteret Islands, among others. Section Three focuses on populations that may be at particular risk, including non-citizens, migrants at sea, those displaced to urban areas, and trapped populations. The concluding section maps the global governance of crisis migration and highlights gaps in current provisions for crisis-related movement across multiple levels"--
-- Setting the Scene / SUSAN F. MARTIN, SANJULA WEERASINGHE and ABBIE TAYLOR -- Conceptualizing "Crisis Migration" : A Theoretical Perspective / JANE McADAM -- Rising Waters, Broken Lives : Experience from Pakistan and Colombia Floods Suggests New Approaches Are Needed / ALICE THOMAS -- Recurrent Acute Disasters, Crisis Migration : Haiti Has Had It All / ELIZABETH FERRIS -- Health Crises and Migration / MICHAEL EDELSTEIN, KHALID KOSER and DAVID L. HEYMANN -- Criminal Violence, Displacement, and Migration in Mexico and Central America / SEBASTIÁN ALBUJA -- Intractability and Change in Crisis Migration : North Koreans in China and Burmese in Thailand / W. COURTLAND ROBINSON -- Environmental Processes, Political Conflict and Migration : A Somali Case Study / ANNA LINDLEY -- Environmental Stress, Displacement and the Challenge of Rights Protection / ROGER ZETTER and JAMES MORRISSEY -- Enhancing Adaptation Options and Managing Human Mobility in the Context of Climate Change / KOKO WARNER AND TAMER AFIFI -- Community Relocations : The Arctic and South Pacific / ROBIN BRONEN -- Something Old and Something New : Resettlement in the Twenty First Century / ANTHONY OLIVER-SMITH AND ALEX DE SHERBININ -- Protecting Non-Citizens in Situations of Conflict, Violence, and Disaster / KHALID KOSER -- Trapped Populations : Controls on Mobility at Times of Crises / MICHAEL COLLYER and RICHARD BLACK -- Policy Adrift : The Challenge of Mixed Migration by Sea / JUDITH KUMIN -- Flight to the Cities: Urban Options and Adaptations / PATRICIA WEISS FAGEN -- The Global Governance of Crisis Migration / ALEXANDER BETTS.
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Case studies; Migration, Internal -- Case studies; Forced migration -- Case studies; Population geography -- Case studies; Humanitarian assistance -- Case studies; Disasters -- Social aspects -- Case studies; Natural disasters -- Social aspects -- Case studies